Bifidobacterium longum 1714™ Strain Modulates Brain Activity of Healthy Volunteers During Social Stress. (July 2019) - Wang, Huiying; Braun, Christoph; Murphy, Eileen F.; Enck, Paul
Abstract : OBJECTIVES: Accumulating evidence indicates that the gut microbiota communicates with the central nervous system, possibly through neural, endocrine, and immune pathways, and influences brain function. B. longum 1714™ has previously been shown to attenuate cortisol output and stress responses in healthy subjects exposed to an acute stressor. However, the ability of B. longum 1714™ to modulate brain function in humans is unclear. METHODS: In a randomized, double-blinded, placebo-controlled trial, the effects of B. longum 1714™ on neural responses to social stress, induced by the "Cyberball game, " a standardized social stress paradigm, were studied. Forty healthy volunteers received either B. longum 1714™ or placebo for 4 weeks at a dose of 1 × 10 9 cfu/d. Brain activity was measured using magnetoencephalography and health status using the 36-item short-form health survey. RESULTS: B. longum 1714™ altered resting-state neural oscillations, with an increase in theta band power in the frontal and cingulate cortex ( P < 0.05) and a decrease in beta-3 band in the hippocampus, fusiform, and temporal cortex ( P < 0.05), both of which were associated with subjective vitality changes. All groups showed increased social stress after a 4-week intervention without an effect at behavioral level due to small sample numbers. However, only B. longum 1714™ altered neural oscillation after social stress, with increased theta and alpha band power in the frontal and cingulate cortex ( P < 0.05) and supramarginal gyrus ( P < 0.05). DISCUSSION: B. longum 1714™ modulated resting neural activity that correlated with enhanced vitality and reduced mental fatigue. Furthermore, B. longum 1714™ modulated neural responses during social stress, which may be involved in the activation of brain coping centers to counter-regulate negative emotions.